I rapporti con l’Islam italiano: dalle proposte d’intesa al Patto nazionale (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Breve premessa - 2. L’ininterrotto dialogo tra il Governo e le comunità islamiche italiane - 3. Il “Patto di condivisione” della Città di Torino e il “Patto nazionale per un Islam italiano” - 4. L’Italia e le misure di contrasto al terrorismo - 5. Conclusione.The relationship with Italian Islam: from the proposals of ‘Intesa’ to the ‘Patto nazionaleABSTRACT: According to statistics, Muslims living in Italy are currently just over 1.6 million. However, despite this significant presence of Muslims on the national territory, the vast world of Islamic associations has not yet managed to sign an Intesa, an agreement that religious minorities can establish to regulate their relations with the Italian state. The reasons why Islam does not have an agreement are mainly two: the absence of an authoritative subject, representative of Italian Islam, able to act as an interlocutor with state institutions and the incompatibility between Islamic cultural values and those of a secular state. Nevertheless, covering all the stages of dialogue between the Italian government and the Islamic associations from the nineties until the conclusion of the Patto nazionale (2017), this work aims to show that the condition of legal vacuum depends on unfounded prejudices towards Islamic culture and on the lack of political will to come to terms with Islam.